Case Report: Management of a congenital intrahepatic portosystemic shunt with portal vein aneurysm in a child using 3D computer-assisted partial right hepatectomy - Liu, Yao; Arief, Johan; Xiu, Wenli; Hao, Xiwei; Wang, Feifei; Xia, Nan; Dong, Qian (Frontiers in Pediatrics, 2024)
Congenital portosystemic shunts (CPSS) are rare pediatric vascular malformations characterized by abnormal development of the portal vein, which is attributed to incomplete embryonic remodeling of the hepatic and surrounding vasculature. CPSS manifests in two main forms: intrahepatic and extrahepatic. This study details the management of a pediatric patient diagnosed with Congenital Intrahepatic Portosystemic Shunt (CIPS) who was referred to our institution. By using a computer-assisted surgical system, the right hepatectomy was successfully performed, guided by precise intraoperative navigation based on three-dimensional reconstructions of enhanced CT imagery. The patient exhibited a favorable postoperative recovery trajectory, with the absence of complications or recurrence throughout the monitoring period.